2020
DOI: 10.1177/1120700020972710
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate of total hip replacements with matched and with mixed components with 10.7 years mean follow-up

Abstract: Background: Mixing and matching components from different manufacturers in total hip arthroplasty is a frequently used off-label praxis. The clinical consequences of this procedure have not been studied in detail. Methods: 860 patients with matched and 1067 patients with mixed primary total hip replacement (THR) components carried out between 1 January 2002 and 31 December 2004, were selected from our Institution registry. The analysis endpoint was set at 1 January 2016. THRs with poorly performing components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In 2018, a prospective study [ 27 ] of 100 patients (105 hips) aged 55 years or younger undergoing a single CTHR showed that the survivorship at a minimum of 22 years with revision for any reason was 97% (95% CI 95–98). In 2022, a prospective study [ 28 ] of 860 patients undergoing a matched CTHR showed that the 14-year overall revision-free survival was 96.0%. Discrepancies between our survival outcomes and those reported in previous studies remain, which may be attributed in part to differences in the patient’s bone and soft tissue conditions [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a prospective study [ 27 ] of 100 patients (105 hips) aged 55 years or younger undergoing a single CTHR showed that the survivorship at a minimum of 22 years with revision for any reason was 97% (95% CI 95–98). In 2022, a prospective study [ 28 ] of 860 patients undergoing a matched CTHR showed that the 14-year overall revision-free survival was 96.0%. Discrepancies between our survival outcomes and those reported in previous studies remain, which may be attributed in part to differences in the patient’s bone and soft tissue conditions [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that it is safe to use unmatched implants for THA as the outcomes in the groups they evaluated compared favourably with those of matched implants in the medium to long term. In addition to these observations from arthroplasty registries, Trebše et al 59 reported that mixing components from different manufacturers did not lead to worse survival rates if the head and stem were provided from the same manufacturer.…”
Section: Recommendationsmentioning
confidence: 93%
“…Trebše et al 59 reported data from their institutional registry that showed that when the head and stem were from different manufacturers, the clinical results were inferior. On the basis of their findings, they recommended that the regulating bodies should introduce a standard taper, with defined tolerances, that would be adopted universally and its use by manufacturers should be compulsory.…”
Section: Recommendationsmentioning
confidence: 99%
“…Life 2022, 12, x FOR PEER REVIEW 14 of 22 nowadays ceramic-on-polyethylene bearing continues to be the workhorse for the majority of cases [80,84]. The reported survival rates of THA are high even with mixed components [85]. Pelvic motion in spine-hip interaction can affect functional acetabular orientation, and consequently functional cup positioning in a THA may be recommended [86].…”
Section: Hipmentioning
confidence: 99%
“…Although different types of hip replacements composed of different materials exist, and the combination of ceramic-on-ceramic bearing is typically reserved for younger patients, metal and nowadays ceramic-on-polyethylene bearing continues to be the workhorse for the majority of cases [ 80 , 84 ]. The reported survival rates of THA are high even with mixed components [ 85 ]. Pelvic motion in spine-hip interaction can affect functional acetabular orientation, and consequently functional cup positioning in a THA may be recommended [ 86 ].…”
Section: Replacementmentioning
confidence: 99%